Evaluation of Transforming Growth Factor Beta-1 Gene 869T/C Polymorphism with Hypertension: A Meta-Analysis - Wenquan Niu (International Journal of Hypertension)
Association between transforming growth factor beta-1 gene (TGFB1) 869T/C polymorphism and hypertension has been widely evaluated, yet with conflicting results. As meta-analysis is a reliable way to resolve discrepancies; I aimed to evaluate this association. Data were available from 9 study populations involving 6151 subjects. Overall, comparison of allele 869C with 869T generated a significant 30% increased hypertension risk (95% confidence interval [95% CI]: 1.11–1.51; P=0.001), which was strengthened for homozygous comparison (869CC versus 869TT) with odds ratio (OR) doubled to 1.62 (95% CI: 1.23–2.14; P=0.001). Stratified analysis by study design demonstrated stronger associations in population-based studies than in hospital-based studies with OR, except in the dominant model, being increased by 7.94–18.61%. Likewise, ethnicity-based analysis exhibited a contradictory association between Asians and Whites. Conclusively, these findings support the notion that TGFB1 gene 869T/C polymorphism may influence the risk of hypertension, especially in Asian populations.